2016
DOI: 10.1007/s10517-016-3570-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Balance in Rats during Adaptation to Swimming Load

Abstract: The main parameters of free radical oxidation and antioxidant defense in the blood plasma, erythrocytes, and homogenates of skeletal muscles, heart, liver, lungs, and kidneys were studied in adult outbred albino male rats with different degree of adaptation to moderate exposure to swimming. The rats were trained to swim regularly over 1 month. Changes in oxidative balance varied in organs and tissues and depended on the level of training. Malonic dialdehyde content in the erythrocytes after swimming increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…). Furthermore, a study comparing a protocol of moderate physical training in both previously trained and untrained rats found that the untrained group had lower levels of anti‐oxidant parameters in response to oxidative stress (Elikov, ). In this regard, we also found that Mn‐SOD and Cu/Zn‐SOD expression were significantly reduced in the carotid artery in the trained group.…”
Section: Discussionmentioning
confidence: 99%
“…). Furthermore, a study comparing a protocol of moderate physical training in both previously trained and untrained rats found that the untrained group had lower levels of anti‐oxidant parameters in response to oxidative stress (Elikov, ). In this regard, we also found that Mn‐SOD and Cu/Zn‐SOD expression were significantly reduced in the carotid artery in the trained group.…”
Section: Discussionmentioning
confidence: 99%
“…It consisted of a swimming exercise in a tank with controlled temperature (31°C) carrying constant loads of 10% of the body weight (17) that were fixed on mice tails. Exhaustion was characterized by the animal losing the coordinated movements and not returning to the surface within 7 s. The animals were submitted to the exercise only once on day 0.…”
Section: Methodsmentioning
confidence: 99%
“…It should be taken into consideration that pro-oxidants detected in blood plasma and erythrocytes reflect the redox state of all components which are included in the motor act during physical exercise. In that sense it's logical to expect the different values of parameters of oxidative stress response measured in heart and in plasma (Elikov 2016). Furthermore, Hu et al (2000) observed no change in the lipid peroxidation level in heart, which may be explained by a shorter period of swimming training (7 days, 45 minutes per day) insufficient to establish positive adaptations to exercise.…”
Section: Levels Of Reduced Glutathione (Gsh)mentioning
confidence: 98%
“…On the contrary, excessive production of ROS leads to a contractile dysfunction which is followed by muscle weakness and fatigue (Powers and Jackson 2008;Rahal et al 2014). It has been established that swimming training causes changes in antioxidant enzymes, alters muscle gene expression, thus contributing to exercise-induced adaptations to skeletal muscle (Venditti and Di Meo 1997;Elikov 2016;Ruzicic et al 2016). However it should be taken into consideration that various factors influence the oxidative stress response to swimming training, such as type of exercise, intensity, duration, gender and age of athletes etc.…”
Section: Introductionmentioning
confidence: 99%